7(5q-6)=2q+1

Simple and best practice solution for 7(5q-6)=2q+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(5q-6)=2q+1 equation:


Simplifying
7(5q + -6) = 2q + 1

Reorder the terms:
7(-6 + 5q) = 2q + 1
(-6 * 7 + 5q * 7) = 2q + 1
(-42 + 35q) = 2q + 1

Reorder the terms:
-42 + 35q = 1 + 2q

Solving
-42 + 35q = 1 + 2q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-2q' to each side of the equation.
-42 + 35q + -2q = 1 + 2q + -2q

Combine like terms: 35q + -2q = 33q
-42 + 33q = 1 + 2q + -2q

Combine like terms: 2q + -2q = 0
-42 + 33q = 1 + 0
-42 + 33q = 1

Add '42' to each side of the equation.
-42 + 42 + 33q = 1 + 42

Combine like terms: -42 + 42 = 0
0 + 33q = 1 + 42
33q = 1 + 42

Combine like terms: 1 + 42 = 43
33q = 43

Divide each side by '33'.
q = 1.303030303

Simplifying
q = 1.303030303

See similar equations:

| Y-2=-5/3(x-4) | | 12x*16x=112 | | N^2=-4n+11 | | 1/2(x-8)-15=-3 | | -5/2(-5) | | 132=24c+32c | | (2+8)-(-10-3)2+4= | | 40-28x+4x^2=0 | | 26/25-14 | | x+20+130+x+150+x-20+140+120=900 | | 3(X+2)+7=2(X+3)+6 | | 6k-2k+6m= | | 8x^4-16x^3+40x^2= | | 17x-y=90 | | 6-2-7+3l= | | 180-x=18+3(90-x) | | (2x+3)(x^2-8x+15)=0 | | 25-0.02w=12.08 | | 0=3x^2+24x-27 | | 40=-.005x^2+1.2x-72.7 | | (4x+8)-(7x-8)= | | 25-0.02=12.08 | | 30-12+45+-10-7= | | -33x(8y)/66x | | 5(x-3)+66=5x-10 | | 8n^2+6n+2=0 | | 4x+106+142+175+98+105+100=900 | | D^3-9=503 | | 40=x^2-240x+14540 | | 3n+3=-255 | | d=16(5) | | 7y+20=2y |

Equations solver categories